An eco-friendly MIL-101@CMCS double-coated dinotefuran for long-acting active release and sustainable pest control. (20th August 2020) - Feng, Pu; Chen, Jinli; Fan, Chaoran; Huang, Guohuan; Yu, Yuzhi; Wu, Jia; Lin, Baofeng
Abstract: Long-acting release systems of pesticide have been shown great potential in agricultural production, as well as environmental protection. However, the current systems for pesticide controlled-release are still many problems, such as the fast drug release in the early stages, and insufficient drug release in late periods, which cannot actively and efficiently control pests. Herein, an eco-friendly active controlled-release system, dinotefuran@FeCl2 (H2 O)2 O(BDC)3 @carboxymethyl chitosan (DNF@MIL-101@CMCS) was successfully prepared by chemical crosslinking. In which, take CMCS as the outer layer, MIL-101 as the inner layer, double layer coated DNF. Its properties of active controlled-release and sustainable anti-pest activity were investigated. As a result, the loading capacity of MIL-101@CMCS to DNF was as high as 24.5%. The DNF of 14.3% was firstly released from the outer layer (CMCS) to achieve early preliminary release. In the late period, the DNF of 83.1% was active released from the inner layer (MIL-101) stimulated by citric acid to achieve long-acting active release. Subsequently, the soil pot experiment results showed that the combination of long and short effect of DNF@MIL-101@CMCS could achieve a long-acting anti-pest activity within 41 days of the entire pest outbreak. Besides, under UV irradiation, the anti-photolysis capacity of DNF protected by MIL-101@CMCS was improved 3.4 times higher than that of uncoated DNF. Therefore, this work provided a promising approach to change the traditional passive release for the active release and improve the utilization rate of pesticide, which is completely consistent with the purpose of cleaner production in agriculture. Graphical abstract: Image 1 Highlights: A double-coated control release system was prepared via chemical crosslinking. Dinotefuran could active release from the composite stimulated by citric acid. The combination of long and short effect makes the system has long-acting anti-pest activity. The control release system was eco-friendly and safe for rice.